Implementation effectiveness of infection prevention and control measures during the first wave of COVID-19: A cross-sectional survey among healthcare workers in four regions of Tanzania - Edward Augustine MAGWE; Modest Diamond VARISANGA; Secilia Kapalata NG’WESHEMI (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: A novel coronavirus disease was officially recognized in Wuhan, China, in December 2019. Tanzania reported its first COVID-19 case on March 16, 2020, at Mount Meru Hospital in the Arusha region, involving a returning national who re-entered the country through Kilimanjaro International Airport. This study was conducted to assess the implementation effectiveness of healthcare facilities’ Infection Prevention and Control (IPC) measures during the first wave of COVID-19 among healthcare workers. This will strengthen the healthcare system’s capacity whenever the disease re-emerges. Methods: This study applied a quantitative analytical cross-sectional survey conducted from 24th of August to 3rd October 2022 in Dar es Salaam, Mwanza, Arusha, and Dodoma regions of Tanzania involving 596 healthcare workers and 40 healthcare facilities. Self-administered questionnaires were used to collect primary data. Frequencies, percentages, Chi-square and logistic regression were analyzed by using the Statistical Package for the Social Sciences (SPSS) version 26. Results: The level of implementation effectiveness was delayed at 91% and fast responses at only 9% of IPC measures. An average of 22.2% of participants said that IPC measures were implemented before the first case was reported in Tanzania. Bivariate logistic regression found a significant relationship in the Arusha region (AOR =15.518, 95% CI, 1.947-123.672, P =0.01) and dispensary in the category of healthcare facilities (AOR =3.876, 95% CI, 1.049-14.314, P =0.042). Discussion and Conclusions: The overall level of implementation effectiveness was maximumly delayed at 91%. It is generally a difficult task in Tanzania to control the outbreak and build hope in combating COVID-19 as a worldwide severe pandemic without strengthening healthcare facilities management and support by taking corrective measures regarding appropriate compliance to infection prevention and control.